Comparative Genome Analysis Reveals Cyanidiococcus gen. nov., A New Extremophilic Red Algal Genus Sister to Cyanidioschyzon (Cyanidioschyzonaceae, Rhodophyta). Issue 6 (21st October 2020) - Liu, Shao‐Lun; Chiang, Yin‐Ru; Yoon, Hwan Su; Fu, Han‐Yi
Abstract : The taxonomic placement of strains belonging to the extremophilic red alga Galdieria maxima has been controversial due to the inconsistent phylogenetic position inferred from molecular phylogenetic analyses. Galdieria maxima nom. inval. was classified in this genus based on morphology and molecular data in the early work, but some subsequent molecular phylogenetic analyses have inferred strains of G. maxima to be closely related to the genus Cyanidioschyzon . To address this controversy, an isolated strain identified as G. maxima using the rbc L gene sequence as the genetic barcode was examined using a comprehensive analysis across morphological, physiological, and genomic traits. Herein are reported the chloroplast‐, mitochondrion‐, and chromosome‐level nuclear genome assemblies. Comparative analysis of orthologous gene clusters and genome arrangements suggested that the genome structure of this strain was more similar to that of the generitype of Cyanidioschyzon, C . merolae than to the generitype of Galdieria, G. sulphuraria . While the ability to uptake various forms of organic carbon for growth is an important physiological trait of Galdieria, this strain was identified as an ecologically obligate photoautotroph (i.e., the inability to utilize the natural concentrations of organic carbons) and lacked various gene models predicted as sugar transporters. Based on the genomic, morphological, and physiological traits, we propose this strain to be a new genus and species, Cyanidiococcus yangmingshanensis . Re‐evaluation of the 18S rRNA and rbc L gene sequences of the authentic strain of G. maxima, IPPAS‐P507, with those of C. yangmingshanensis suggests that the rbc L sequences of " G. maxima " deposited in GenBank correspond to misidentified isolates.